The moral values and their role in building the Islamic personality at the individual and community levels with the personality of Joseph, peace be upon him, as a model - Awad, Dr. Ruba Hisham Awad (Sulaimani Journal for Humanities, 2026)
This study examines moral values and their role in shaping the Islamic character at both the individual and societal levels, drawing from the character of Prophet Yusuf (Joseph), peace be upon him, as an exemplary model to be emulated. A number of references were reviewed to extract and deduce key insights from Surah Yusuf related to the research topic, followed by an analysis aimed at highlighting the most significant moral values that educators can instill in the younger generation and embed in their personalities, as they are the builders and pillars of society. Additionally, the study explores the importance of these derived values in maintaining the cohesion of any society whose members uphold noble ethical principles, making them more united and harmonious. The study comprises an introduction and six main sections that address the subject from all angles, along with various subsections as required by the theoretical framework. It concludes with a summary, key findings, and final recommendations
Keywords: Moral values; Islamic character; Prophet Joseph (peace be upon him); Individual; Society